2016
DOI: 10.1016/j.celrep.2016.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RORγT Skews TCRα Gene Rearrangement and Limits T Cell Repertoire Diversity

Abstract: Recent studies have elucidated the molecular mechanism of RORγT transcriptional regulation of Th17 differentiation and function. RORγT was initially identified as a transcription factor required for thymopoiesis by maintaining survival of CD4CD8 (DP) thymocytes. While RORγ antagonists are currently being developed to treat autoimmunity, it remains unclear how RORγT inhibition may impact thymocyte development. In this study, we show that in addition to regulating DP thymocytes survival, RORγT also controls gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…To achieve the desired ear phenotype in these strains, it is likely that higher doses of IL‐23 MC would be required. To this end, another group injected 8 μg of IL‐23 MC to C57BL/6 mice to induce ear skin inflammation …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve the desired ear phenotype in these strains, it is likely that higher doses of IL‐23 MC would be required. To this end, another group injected 8 μg of IL‐23 MC to C57BL/6 mice to induce ear skin inflammation …”
Section: Resultsmentioning
confidence: 99%
“…This methodology has been used to investigate IL‐23 associated bone and joint pathology, and it was also noted to cause histological skin thickening on day 35 following administration of 3 μg IL‐23 MC to B10.RIII mice . Another group administrated 8 μg of IL‐23 MC to C57BL/6 mice and induced a significant increase in IL‐23/IL‐17 pathway genes/proteins as well as histological psoriasis‐like scores on day 9, which were reduced by an ROR γ T antagonist . Hydrodynamic delivery of 8 μg IL‐17 MC has also been shown to cause skin inflammation in C57BL/6 mice 7 weeks post‐transfection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cua and colleagues recently reported that pharmacological inhibition of RORγt by allosteric RORγt antagonists, MRL-871 or MRL-248 (structurally similar to MRL-871 but with improved in vivo pharmacodynamics) resulted in rapid DP thymocyte apoptosis within 3 days and immediate changes in gene expression within 2 hours of drug treatment 8 . Through RNA-Seq analysis of changes in gene expression in DP cells shortly after RORγt inhibition (2 hr) or with RORγt-overexpression, the authors identified 33 genes, including Bcl-x L , Plxnd1 and Sla , that are known to be involved in cell apoptosis and survival, cell migration and positive selection, respectively.…”
mentioning
confidence: 99%
“…Interestingly, RORγt inhibition resulted in reduced frequency of myelin oligodendrocyte glycoprotein (MOG)-specific “self-reactive” CD4 + T cells in approximately half of the RORγt antagonist-treated mice 8 . Consequently, RORγt antagonist pre-treatment delayed the autoimmune progression in the experimental autoimmune encephalomyelitis (EAE) model induced by MOG immunization, even though the RORγt antagonist was no longer present during the course of disease induction.…”
mentioning
confidence: 99%